2002
DOI: 10.1046/j.1442-2026.2002.t01-1-00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis and driving: A new perspective

Abstract: Cannabis and driving is an emerging injury-prevention concern. The incidence of driving while affected by cannabis is rising in parallel with increased cannabis use in the community. Younger drivers are at particular risk. Improvements in research methodology, technology and laboratory testing methods have occurred in the last 10 years. These cast doubt on earlier results and conclusions. Studies now show that cannabis has a significant impairing effect on driving when used alone and that this effect is exagge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…According to Niedbala the cannabis can be detected in saliva up to 30 hours after the consumption to certain doses [12]. According to other authors is detected between 2-10 hours [13,14]. Laloup et al [15] found good correlation between the THC in saliva and plasma in 139 subjects what agrees with other publications though protocols of analysis and values of cut-off established in every study can be different and may affect the results [16].…”
Section: Discussionsupporting
confidence: 78%
“…According to Niedbala the cannabis can be detected in saliva up to 30 hours after the consumption to certain doses [12]. According to other authors is detected between 2-10 hours [13,14]. Laloup et al [15] found good correlation between the THC in saliva and plasma in 139 subjects what agrees with other publications though protocols of analysis and values of cut-off established in every study can be different and may affect the results [16].…”
Section: Discussionsupporting
confidence: 78%
“…Some investigators have reported subjective and impaired behavioral effects for up to 3 h after the end of smoking but could not find significant effects the following day (7, 28 -30 ). Others have reported decrements in cognitive function and complex performance tasks for more than 24 h ( [31][32][33]. A consensus panel of experts that met to determine the current state of knowledge for effects of cannabis on driving performance reported that "most behavioral and physiological effects return to baseline levels within 3-5 h after drug use, although some investigators have demonstrated residual effects in specific behaviors such as complex divided attention tasks for up to 24 h" (23 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been suggested that, unlike users of alcohol, cannabis users are aware of their level of intoxication and compensate for the effects by becoming very cautious, resulting in a decrease in the speed and the frequency of overtaking, as well as an increase in the following distance (64). It is recognized that cannabis may have significant effects on driving ability, with exaggerated effects in the presence of alcohol (65). Seizures: Data on the risk of epileptic seizures following cannabis use were nonconclusive (66).…”
Section: Acute Effectsmentioning
confidence: 99%